2023
DOI: 10.1126/sciadv.ade7002
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of neuropathic pain by microglial Orai1 channels

Abstract: Microglia are important mediators of neuroinflammation, which underlies neuropathic pain. However, the molecular checkpoints controlling microglial reactivity are not well-understood. Here, we investigated the role of Orai1 channels for microglia-mediated neuroinflammation following nerve injury and find that deletion of Orai1 in microglia attenuates Ca 2+ signaling and the production of inflammatory cytokines by proalgesic agonists. Conditional deletion of Orai1 attenuated microglial p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 66 publications
0
10
0
Order By: Relevance
“…In line with these hypotheses, our further investigations revealed that HF10 SCS profoundly suppresses immune responses induced by nerve injury by modulating proinflammatory microglia in the SDH. This finding indicated that microglia are highly responsive to HF10 SCS, possibly due to the delivery of a higher charge per second compared to Con SCS, which alters membrane potentials and intracellular chemical signaling in microglia, such as Ca2+, an important messenger 36,37 that triggers multiple downstream signaling pathways (eg, Kaiso‐P2X7R in our case). Other studies investigating electric stimulation for treating neurodegenerative disorders have also demonstrated direct modulatory effects on microglia, previously considered “nonresponsive” by using different stimulation parameters, which showed reduced immune responses and increased anti‐inflammatory effects 38–40 .…”
Section: Discussionmentioning
confidence: 70%
“…In line with these hypotheses, our further investigations revealed that HF10 SCS profoundly suppresses immune responses induced by nerve injury by modulating proinflammatory microglia in the SDH. This finding indicated that microglia are highly responsive to HF10 SCS, possibly due to the delivery of a higher charge per second compared to Con SCS, which alters membrane potentials and intracellular chemical signaling in microglia, such as Ca2+, an important messenger 36,37 that triggers multiple downstream signaling pathways (eg, Kaiso‐P2X7R in our case). Other studies investigating electric stimulation for treating neurodegenerative disorders have also demonstrated direct modulatory effects on microglia, previously considered “nonresponsive” by using different stimulation parameters, which showed reduced immune responses and increased anti‐inflammatory effects 38–40 .…”
Section: Discussionmentioning
confidence: 70%
“…However, at least one study suggests a role for SOCE in nociception mediated by dorsal root ganglia (DRG) neurons, in which global Orai1 deficiency in mice decreases allodynia ( 21 ). SOCE is also associated with neuropathic pain mediated by the production of inflammatory cytokines and pain mediators in microglia ( 54 ). Therefore, it was plausible that SOCE deficiency might also affect pain in our model.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has become clear that SOCE and the proteins associated with it are expressed and functional in neurons and glial cells (Bollimuntha et al., 2018; Moccia et al., 2015). In addition, modifications of SOCE and Ca 2+ homeostasis have been associated with multiple perturbations of the nervous system such as Alzheimer disease (AD), Huntington disease (HD) and chronic pain (Bollimuntha et al., 2018; Popugaeva et al., 2015; Popugaeva et al., 2017; Tsujikawa et al., 2023; Wegierski & Kuznicki, 2018; Zhang & Hu, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In mouse microglia, a recent study has shown that Orai1‐mediated SOCE drives inflammatory cytokine production and microglial proliferation following stimulation with proalgesic molecules or in vivo after nerve injury. Conditional deletion or pharmacological Orai1 inhibition was also able to alleviate allodynia in male but not female mice, indicating a sexual dimorphism in the regulation of pain sensation by microglial SOCE (Tsujikawa et al., 2023).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation